Peningkatan Pemahaman Hak Konstitusional Memperoleh Layanan Administrasi Kependudukan Guna Mendapatkan Bantuan Hukum Gratis Bagi Anak Di SMAN 16 Pekanbaru - Andrizal, Andrizal; Asnawi, Eddy; Prayoga, Tatang; Javari, Zulhian Sultan; Juliandra, Muhammad Davi; Harman, Muhammad Sambu (Institut Bisnis dan Teknologi Pelita Indonesia, 2025)
The partner’s main problem, in this case the students of SMAN 16 Pekanbaru, lies in their limited knowledge and understanding of their constitutional rights to obtain administrative services in the form of civil registration documents, as well as the existence of government programs that provide free legal aid for underprivileged citizens. The target group of this community service activity consists of students who predominantly reside in the sub-districts of Rumbai and East Rumbai, Pekanbaru City—areas that are vulnerable to legal issues arising from juvenile delinquency such as drug abuse, brawls, theft, and other misconduct. This legal awareness program is expected to improve the knowledge and understanding of the target audience regarding the identified partner problems. The solution offered and mutually agreed upon by the proposing team and the partner institution is the implementation of socialization activities through the delivery of materials and discussions in the form of legal counseling. The method employed in this activity is the lecture method, in which the speaker presents the material, and participants are given the opportunity to engage in an open question-and-answer session. The detailed steps of the method include: (1) delivery of materials, and (2) interactive dialogue, which functions as a brainstorming session to gather input in the form of problems, aspirations, suggestions, ideas, and solutions from the participants.Partner participation in this activity includes expressing willingness to collaborate, providing the necessary time and venue, and mobilizing the community as the target audience. The expected outcomes of this community service activity are: for the partners, an increase in knowledge and understanding regarding the fulfillment of constitutional rights to obtain civil registration services and access free legal aid; and for the community service team, the fulfillment of their obligation under the Tri Dharma of Higher Education.